PERTUMBUHAN DAN PRODUKSI JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA PERBEDAAN KOMPOSISI MEDIA TANAM - Nunilahwati, Haperidah; Syafrullah, Syafrullah; Kurniawan, Rendy (Universitas Muhammadiyah Palembang, 2020)
Fungi are plants that cannot carry out photosynthesis because they do not have chlorophyll. The purpose of this study was to determine the ratio of tankos and bran media as a planting medium to the growth and production of oyster mushroom (Pleurotus ostreatus) plants. The research was conducted from May to July 2019 in Talang Buluh Village, Talang Kelapa District, Banyuasin Regency, South Sumatra Province. The research method used a completely randomized design (CRD) with 5 treatments and 5 replications. The results showed that the composition of the growing media 70% tankos, 27% bran, 3% lime was the best treatment for the growth and production of oyster mushrooms with a fresh weight of 320.26 g/baglog.